Resource allocations of Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) in response to socio-sexual environment during immature and adult stages : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Entomology at Massey University, Palmerston North, New Zealand - Liu, Junyan (Massey University, 2023)
Animals adjust their investment in different life history traits according to their surroundings to maximise their fitness. Using a polygamous insect, the Mediterranean flour moth Ephestia kuehniella Zeller, which produces fertile eupyrene and infertile apyrene sperm, I investigated resource allocation strategies employed by males in response to socio-sexual cues during the adult and juvenile stages. I demonstrate that adult males raised their lifetime production and ejaculation of both eupyrenes and apyrenes after detecting either acoustic or chemical cues from adult rivals with combined cues strengthening such response, and that rival-experienced males could remember the sperm competition risk for most of their reproductive life. I manipulated juvenile socio-sexual settings and then examined their sperm production and ejaculation as well as survival, body and testis size, and mating behaviour. I provided the first evidence that juvenile social cues from conspecific larvae, pupae or adults had lasting impacts on lifetime sperm production and allocation. Adults from group-reared larvae, regardless of sex ratio, had smaller testes but produced more eupyrenes at emergence than from singly reared ones, and that body size and apyrene numbers remained the same across treatments. Male pupae had similar testis size but increased production of both eupyrenes and apyrenes at emergence in response to cues from conspecific pupae irrespective of sex. Late instar male larvae were able to detect cues from adult rivals and subsequently produced more sperm of both types at emergence, but adult cues had no effect on body and testis size. Juvenile socio-sexual environment had significant effects on sperm production and ejaculation during adult stage. My study indicates that after their late instar larvae were exposed to juvenile or adult rivals, adults produced and ejaculated more eupyrenes and apyrenes in their lifetime and had shorter mating latency. However, rival exposure had no effect on males’ mating frequency and longevity. Knowledge generated here enhances our understanding of how males of a polygamous insect calibrate their resource investment in response to dynamic social environment.
Listed in 2023 Dean's List of Exceptional Theses
Keywords: Mediterranean flour moth; Spermatozoa; Generative organs; Sexual behavior; Dean's List of Exceptional Theses; 310907 Animal physiological ecology